2017
DOI: 10.1021/acsami.7b05372
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination of an Alumina Surface: Modeling Aluminum–Fluorine Reaction Mechanisms

Abstract: Density functional theory (DFT) calculations were performed to examine exothermic surface chemistry between alumina and four fluorinated, fragmented molecules representing species from decomposing fluoropolymers: F, HF, CHF, and CF. The analysis has strong implications for the reactivity of aluminum (Al) particles passivated by an alumina shell. It was hypothesized that the alumina surface structure could be transformed due to hydrogen bonding effects from the environment that promote surface reactions with fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 35 publications
1
40
1
Order By: Relevance
“…The SQ nAl + PVDF exhibits a two-stage pressure rise: an initial spike followed by a slower rise suggesting a two-stage ignition and reaction behavior. In this case, the extended rise time to peak pressure may allow HF gas generated in the conned cell to react with Al and favor production of condensed phase AlF 3 as shown by Padhye et al 26 For the second-stage in the SQ nAl + PVDF reaction there is similarity in the pressure history for the UN nAl + PVDF reaction with a plateau in pressure following the peak. The shoulder could be related to gas generation behavior which is more rate limited in these two lms and may be produced in stages.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The SQ nAl + PVDF exhibits a two-stage pressure rise: an initial spike followed by a slower rise suggesting a two-stage ignition and reaction behavior. In this case, the extended rise time to peak pressure may allow HF gas generated in the conned cell to react with Al and favor production of condensed phase AlF 3 as shown by Padhye et al 26 For the second-stage in the SQ nAl + PVDF reaction there is similarity in the pressure history for the UN nAl + PVDF reaction with a plateau in pressure following the peak. The shoulder could be related to gas generation behavior which is more rate limited in these two lms and may be produced in stages.…”
Section: Resultsmentioning
confidence: 94%
“…Generalization of eqn (20)-(23) for the case with delamination during quenching without creep is shown in eqn (24)- (26).…”
Section: Stresses and Strains Aer Annealing Followed By Cooling Withmentioning
confidence: 99%
“…This is of significant practical importance for the disadvantages of nanoparticles mentioned above. Pantoya et al [23,[27][28][29] investigated factors affecting pre-ignition reaction (PIR, the initial exothermic reaction between metal and fluorocarbon) and found that alumina surface structure could be transformed due to hydrogen bonding effects resulting in enhancing in oxidation reactivity of Al in Al/PTFE mixtures. Dreizin et al [19] studied much mechanical milling prepared reactive materials.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present investigation was to develop an economical bio‐adsorbent for the sequential removal of Al(III) and fluoride from contaminated water by optimizing various physicochemical parameters by integral optimization technique, RSM, and to study the thermodynamics, isotherms, and kinetics of the sorption process (Padhye, Aquino, Tunega, & Pantoya, ).…”
Section: Introductionmentioning
confidence: 99%